Implementation of a Virtual Tour for SMK Istiqomah Muhammadiyah 4 Samarinda City Using a 360° Camera - Muhammad Akmal Amrullah Ali; Wahyuni Wahyuni; Jundro Daud Hasiolan (STMIK Widya Cipta Dharma, 2025)
The rapid development of digital technology has encouraged educational institutions to adapt and innovate in promoting their school profiles. This study discusses the implementation of Virtual Tour technology at SMK Istiqomah Muhammadiyah 4 Kota Samarinda by utilizing a 360° camera as a medium to introduce the school environment interactively. The purpose of this research is to provide an engaging and realistic virtual experience that allows users to explore school facilities without being physically present on site. This study employs the Multimedia Development Life Cycle (MDLC) method, which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. The implementation process includes capturing 360° panoramic images using a 360° camera, processing and integrating the images through the Kuula platform, and publishing the Virtual Tour on the school’s official website. Testing was conducted using the black-box method and beta testing involving teachers, students, and prospective students to evaluate usability and user experience. The results show that the developed Virtual Tour application functions properly, runs smoothly on various devices, and provides a positive exploration experience for users. Most respondents stated that the application is easy to use, informative, and visually appealing. The implementation of this Virtual Tour is considered effective in increasing the school’s attractiveness, strengthening its modern institutional image, and supporting digital-based promotional strategies in today’s technological era.